2011
DOI: 10.1042/cs20110259
|View full text |Cite
|
Sign up to set email alerts
|

Acute simvastatin increases endothelial nitric oxide synthase phosphorylation via AMP-activated protein kinase and reduces contractility of isolated rat mesenteric resistance arteries

Abstract: Statins can have beneficial cholesterol-independent effects on vascular contractility, which may involve increases in the bioavailability of NO (nitric oxide) as a result of phosphorylation of eNOS (endothelial NO synthase). Although this has been attributed to phosphorylation of Akt (also known as protein kinase B), studies in cultured cells have shown that statins can phosphorylate AMPK (AMP-activated protein kinase); it is unknown whether this has functional effects in intact arteries. Thus we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 42 publications
6
47
0
Order By: Relevance
“…These anti-migratory and anti-proliferative effects of AMPK are consistent with the findings of others in human and rodent ASM [25,26]. Moreover, complementing its growth inhibitory actions AMPK has been shown to elicit vascular relaxation [6,27] and to maintain vascular barrier function during hypoxia [28], thus making it an attractive candidate for further study in the vasculature.…”
Section: Discussionsupporting
confidence: 86%
“…These anti-migratory and anti-proliferative effects of AMPK are consistent with the findings of others in human and rodent ASM [25,26]. Moreover, complementing its growth inhibitory actions AMPK has been shown to elicit vascular relaxation [6,27] and to maintain vascular barrier function during hypoxia [28], thus making it an attractive candidate for further study in the vasculature.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Aoki et al reported that, besides the NOS3 mRNA up-regulation, fluvastatin also modified the phosphorylation pattern of endothelial cells 12 . A similar posttranslational modification was observed in isolated rat arteries treated with simvastatin 13 , which also caused an enhanced phosphorylation of eNOS at the Ser 1177 through regulation of the PKB/Akt, a process that leads to a higher enzyme activity and increased NO release 14 .…”
Section: Discussionsupporting
confidence: 63%
“…Atorvastatin has also been shown in ECs to increase eNOS phosphorylation at Ser-633 in an adenosine monophosphate activated protein kinase (AMPK)-mediated way (79). Moreover, ex vivo incubation of rat mesenteric resistance arteries with simvastatin induces rapid AMPKmediated eNOS phosphorylation at Ser-1177 (93). This leads to improved endothelium-dependent vasorelaxation in myograph chamber vasomotor studies, an effect reversed both by inhibition of eNOS by N-nitro-l-arginine methyl ester (LNAME) and by co-incubation with mevalonate.…”
Section: Effects Of Statins On Enosmentioning
confidence: 99%